Infant mortality and low birth weight in cities of Northeastern and Southeastern Brazil - Antônio Augusto Moura da Silva; Heloísa Bettiol; Marco Antônio Barbieri; Valdinar Sousa Ribeiro; Vânia Maria de Farias Aragão; Luiz Gustavo Oliveira Brito; Márcio Mendes Pereira
OBJECTIVE: To compare estimates of low birth weight (LBW), preterm birth, small for gestational age (SGA), and infant mortality in two birth cohorts in Brazil. METHODS: The two cohorts were performed during the 1990s, in São Luís, located in a less developed area in Northeastern Brazil, and Ribeirão Preto, situated in a more developed region in Southeastern Brazil. Data from one-third of all live births in Ribeirão Preto in 1994 were collected (2,839 single deliveries). In São Luís, systematic sampling of deliveries stratified by maternity hospital was performed from 1997 to 1998 (2,439 single deliveries). The chi-squared (for categories and trends) and Student t tests were used in the statistical analyses. RESULTS: The LBW rate was lower in São Luís, thus presenting an epidemiological paradox. The preterm birth rates were similar, although expected to be higher in Ribeirão Preto because of the direct relationship between preterm birth and LBW. Dissociation between LBW and infant mortality was observed, since São Luís showed a lower LBW rate and higher infant mortality, while the opposite occurred in Ribeirão Preto. CONCLUSIONS: Higher prevalence of maternal smoking and better access to and quality of perinatal care, thereby leading to earlier medical interventions (cesarean section and induced preterm births) that resulted in more low weight live births than stillbirths in Ribeirão Preto, may explain these paradoxes. The ecological dissociation observed between LBW and infant mortality indicates that the LBW rate should no longer be systematically considered as an indicator of social development.